Vehicle battery fires : why they happen and how they happen - Barnett, Gregory J. (SAE International, 2017)
The main focus of the book resides in looking at differences in failure modes between DC and AC systems, general types of battery and electrical failure modes leading to fire, how to interpret electrical fire, determination of the primary failed part, and other skills the investigating engineer will require to perform technical failure mode analysis.
Keywords: Electric automobiles -- Batteries.; Automobiles -- Fires and fire prevention.; elektronické knihy; electronic books